PELATIHAN KOMUNIKASI ORGANISASI DAN PUBLIC SPEAKING BAGI PENGURUS OSIS SMKN 1 TANGERANG SELATAN UNTUK MENINGKATKAN KOMPETENSI KEPEMIMPINAN SISWA: ORGANIZATIONAL COMMUNICATION AND PUBLIC SPEAKING TRAINING FOR OSIS MANAGEMENT OF SMKN 1 SOUTH TANGERANG TO IMPROVE STUDENTS' LEADERSHIP COMPETENCIES - Alvin Praditya; Muhammad Firdaus; Rintan Melvayanda Akasah (JBMP: Jurnal Bhakti Muhammadiyah Papua, 2026)
Training in organizational communication and public speaking for the student council members of SMKN 1 South Tangerang aimed to improve students’ leadership competencies. The implementation methods included lectures, interactive discussions, practice sessions, and simulations, which were conducted on April 29, 2026. The results showed an improvement in participants’ understanding of organizational communication, confidence in public speaking, reduction in communication anxiety, and technical public speaking skills. This training made a positive contribution to the development of student leadership by making the student council members more communicative, confident, and responsible. Kata kunci: komunikasi organisasi, public speaking, kepemimpinan siswa